Collection and conservation of medicinal and aromatic plants resources - Abraham, Z. (Open Access Journal of Medicinal and Aromatic Plants, 2011)
(Abstract selected from presentation in National Conference on Biodiversity of Medicinal and Aromatic Plants: Collection, Characterization and Utilization, held at Anand, India during November 24-25, 2010)Plant genetic resources have made substantial contributions to the domestication, utilization and improvement of all kinds of crops including medicinal and aromatic plants. Collection, characterization and  their efficient utilization are keys to efficient management of any kind of genetic resource including those of medicinal and aromatic plants. Modern techniques offer the opportunity for collecting, rapid propagation, medium and long-term storage and distribution of germplasm. Complementary  strategies are significant for conservation, particularly of medicinal and aromatic plants as we come across a wide spectrum of species with orthodox or recalcitrant or intermediate seed storage behaviour or exclusively vegetatively propagated plants. Collections from different and widely placed areas will greatly enhance the existing collections in genebanks by providing back-ups in case of losses through diseases, insects and environmental stresses and weather changes. The major objectives of conservation programmes are to provide safety against loss of genetic resources and to make these resources available for crop improvement at present and in the future. Each strategy for conservation has to offer relatively greater safety and cost effectiveness. Any useful plant can be considered for conservation but medicinal plants with known biological activities and chemical constituents responsible for such activities if influenced by agro-ecological situations needs to be conserved in ideal situations to avoid loss of essential compounds responsible for biological actions. However, prioritisation of species is essential to make full use of any particular strategy with justification. Modification of the environment and particularly associations combined with any treatment exercised for survival or increasing productivity needs to be approached cautiously. This lecture will review the available information on collection, characterization, utilization, conservation and documentation of genetic resources belonging to medicinal and aromatic plants.